PENGARUH MOTIVASI KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN STBA - Susilo Wulandari (POLITEKNIK LP3I JAKARTA, 2019)
In this research, Problem formulation is any influence of work motivation and work ability simultaneously and partially to employee performance at STBA. The hypothesis proposed is the influence of work motivation and work ability simultaneously and partially on employee performance at STBA. Type of descriptive research with questionnaire as data source. The population in this study is all employees STBA, totaling 71 employees. The sample in this research is 42 employees, using Slovin formula with sampling technique used. Probability sampling is sampling technique that gives equal opportunity for each population to be selected as a member of the sample and the method used is simple random sampling. Tool of analysis in this research is doubled linear regression. Based on simultaneous test (F test) obtained value of F count equal to 19,104 bigger than F table value (3,252) so that its decision reject Ho and accept Ha. This means that simultaneously the independent variables (work motivation and work ability) affect Employee Performance. Based on the partial test results (t test) calculate the work motivation variable of 3.735. By looking at the position of t arithmetic (3.735) is greater than t table (2.026) then t arithmetic is the rejection of Ho and acceptance of Ha so that his decision reject Ho and accept Ha. This means that partially Work Motivation variables affect employee performance. The value of t arithmetic working ability variable of 3.328. By looking at the position of t arithmetic (3.328) greater than t table (2.026) then t arithmetic is in the rejection region Ho and acceptance of Ha so that his decision reject Ho and accept Ha. This means that partially Work Ability variables affect Employee Performance. Associated with the results of hypothesis testing, then the results of this study showed the influence of work motivation and work ability either simultaneously or partially. The effect of the research results showed a positive direction, which means that better work motivation and the ability of good work will improve employee performance. Therefore it is expected that the management of STBA to review the efforts to improve motivation factors and employee work skills so as to achieve maximum employee performance.Key words : Work Motivation, Working Ability, Employee Performance